Pedagogical Resilience of Elementary School Teachers in the Context of Marginalized School Governance (Case Study of Samudrajaya 03 State Elementary School, Bekasi) - Lilis Suwandari; Ajat Sudrajat; Ade Hernawan; Saoqy Noor Muhammad Isa; Sahru Abdul Muhsin (FKIP - Universitas Riau, 2026)
This study examines the pedagogical resilience of elementary school teachers within the context of marginal school governance through a qualitative case study conducted at State Elementary School Samudrajaya 03, Bekasi, Indonesia. Marginal schools commonly operate under weak governance structures, limited resources, and minimal institutional support conditions that potentially constrain pedagogical practices. However, this study finds that teachers do not merely endure these constraints but actively develop adaptive and reflective pedagogical strategies. Data were collected through in-depth interviews, classroom observations, and document analysis. The findings indicate that pedagogical resilience is manifested through conscious instructional adaptation, curriculum negotiation, and contextual classroom management. Teachers exercise professional agency by strategically adjusting pedagogical practices to sustain meaningful learning despite structural limitations. Conceptually, this study positions pedagogical resilience not as an individual psychological trait, but as a form of professional agency enacted through pedagogical practice under conditions of weak school governance. Rather than seeking statistical generalization, the study offers analytical generalization that contributes to the discourse on teacher resilience and school governance in marginalized educational settings. The findings also have implications for educational policy and professional development initiatives aimed at strengthening pedagogical capacity in marginal schools.